Yield performance of strawberry genotypes - Chowhan, S; Hossain, MM; Hoque, MA; Rasul, G; Roni, MS (Bangladesh Journal of Agricultural Research, 2016)
Five strawberry genotypes ('Rabi 3', 'Camarosa', 'BARI Strawberry 1', 'BADC Strawberry' and 'Festival') were evaluated for their field performance. The maximum number of leaves/plant (14.2), canopy spread (31.82 cm) and runners/plant (7.2) were found with 'Camarosa', 'Festival' and 'Rabi 3' respectively. Festival took the lowest number of days to flower initiation (32.5). The highest number of flowers (23.64) and fruits/plant (19.98) were found in 'Camarosa'. The heaviest (21.83 g) and the largest sized individual fruit (1539.31 mm2) were produced by 'Festival'. Fruit TSS (%) was the highest (15.83) in BARI Strawberry 1. Genotype 'Festival' gave the highest fruit yield (12.94 t/ha) and 'BADC Strawberry' yielded the lowest (6.15 t/ha). Considering growth, yield and quality of fruit, genotypes 'Festival' and 'Camarosa' were found promising under the climatic condition of Salna. Bangladesh J. Agril. Res. 41(3): 481-489, September 2016